2018
DOI: 10.1177/0276146718796913
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Systems and Market Failure

Abstract: The paper seeks to re-examine a classic piece of macromarketing scholarship which dealt with market failures. That analysis was based on a transactional approach to markets, rather than a systems approach. Having become more prominent in the macromarketing literature since that time, marketing systems are the focus of the present analysis. The paper looks at six types of market failure: imperfect competition, entry barriers, externalities, imperfect information, inequality, and transaction costs. Definitions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 42 publications
0
48
0
4
Order By: Relevance
“…Dark sides are another way of describing externalities and internalities. Redmond (2018) suggests that negative internalities resulting in unanticipated costs may be more harmful to marketing systems than to traditional transactional markets. Redmond also points out how “Over-reliance on other system members may produce several modes of negative internalities” and “opportunistic behavior or fraud by system members can harm others in the system” (p. 417), both of which we substantiate in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dark sides are another way of describing externalities and internalities. Redmond (2018) suggests that negative internalities resulting in unanticipated costs may be more harmful to marketing systems than to traditional transactional markets. Redmond also points out how “Over-reliance on other system members may produce several modes of negative internalities” and “opportunistic behavior or fraud by system members can harm others in the system” (p. 417), both of which we substantiate in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As such, our analysis informs the ongoing and recent macromarketing discussion about the functioning and possible failure of marketing systems. Redmond (2018), for example, clarifies the distinction between market failure—external performance, usually tied to consumer welfare—and market decline—internal performance related to growth and sales. Our analysis has shown that there can be dark sides whether an alternative economy declines or thrives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their seminal work continues to influence macromarketing scholarship, and the wider academy, particularly in the areas of externalities (e.g. Padela, Wooliscroft, and Ganglmair-Wooliscroft 2020; Redmond 2018; Williams, Davey, and Johnstone 2020), application of dynamic systems modelling (e.g. Domegan et al 2020, 2019), considering the marketing/market systems in particular times and places (e.g.…”
Section: Macromarketing’s Potential Contributions To Systems Researchmentioning
confidence: 99%
“…A competição pelos melhores resultados decorrentes das transações econômicas regulará, de forma impessoal, o comportamento dos preços, sendo o equilíbrio de interesses entre produtores e compradores, a melhor situação de alocação de recursos para ambos. Trata-se, por fim, de um mecanismo natural sobre o qual pouca intervenção estatal deverá ocorrer para viabilizar a situação de livre comércio (ARENDT, 1983;VAREY, 2010;REDMOND, 2018).…”
Section: Os Estudos Construtivistas De Mercado Em Marketing: Origens unclassified